2020
DOI: 10.1007/s11049-020-09476-w
|View full text |Cite
|
Sign up to set email alerts
|

Exclusivity! Wh-fronting is not optional wh-movement in Colloquial French

Abstract: This article revisits the long-standing issue of the alternation between wh-in-situ and wh-ex-situ questions in French in the light of diglossia and cross-linguistic data. A careful preliminary examination of the numerous wh-structures in Metropolitan French leads us to focus on Colloquial French, which undoubtedly displays both wh-in-situ and wh-ex-situ questions. Within this dataset, wh-ex-situ questions without the est-ce que ‘is it that’ marker are more permissive than in-situ regarding weak-islandhood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Type 3 is presuppositional-specific (the wh-phrase forms its own prosodic phrase; Vergnaud and Zubizarreta, 2005). 8 In adult speech, Faure and Palasis (2021) showed that wh-ex-situ is favoured by the presence of a contrastive feature whose specific semantics is exclusive, meaning that the question conveys the presupposition that at least one of the contextually available answers is a priori excluded.…”
Section: Outliers To the Correlation Between Fixed Be Form And Wh-in-...mentioning
confidence: 99%
“…Type 3 is presuppositional-specific (the wh-phrase forms its own prosodic phrase; Vergnaud and Zubizarreta, 2005). 8 In adult speech, Faure and Palasis (2021) showed that wh-ex-situ is favoured by the presence of a contrastive feature whose specific semantics is exclusive, meaning that the question conveys the presupposition that at least one of the contextually available answers is a priori excluded.…”
Section: Outliers To the Correlation Between Fixed Be Form And Wh-in-...mentioning
confidence: 99%
“…This structure is frequently used in spoken colloquial French (Coveney, 2011;Faure and Palasis, 2021;Hamlaoui, 2011;Koch and Oesterreicher, 2011, a.o.). As wh-in-situ questions contain a question word, they are morphosyntactically marked as interrogative sentences.…”
Section: Introductionmentioning
confidence: 99%
“…The French interrogative system remains a topic of interest in research on both first (L1) and second (L2) language acquisitions of French (Faure and Palasis 2021;Hamlaoui 2011;Li 2021;Zwanziger 2008). Its complexity is widely recognized and has been identified as a potential challenge for L2 learners (Donaldson 2016;Zwanziger 2008).…”
Section: Introductionmentioning
confidence: 99%